Participation of private organisations in the development of physical culture and sport at regional level - Rapoport, L.A.; Terentev, A.E.; Tomilova, S.V.; Rapoport, A.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify ways to increase the involvement and effectiveness of non-governmental organisations in the development of physical culture and sport at the regional level, using the Sverdlovsk Oblast as an example. Methods and structure of the study. Theoretical and empirical methods were used in the course of the study. The study is based on the examination and analysis of statistical data from statistical observation form No. 1-FK, data from the Ministry of Physical Culture and Sport of the Sverdlovsk Oblast, the Federal Tax Service, federal and regional regulatory, legal and strategic documents in the field of physical culture and sport for the period from 2017 to 2024. Results and conclusions. The study identified approaches to increasing the involvement and effectiveness of non-governmental organisations in the development of physical culture and sport in the Sverdlovsk Oblast, based on the need to improve regulatory and legal regulation, amend legislation, remove financial and organisational restrictions for non-governmental organisations, etc.